DEE 2021
DOI: 10.21543/dee.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic and family structure changes on income distribution in Hungary and OECD countries

Abstract: This paper analyses the impact of socio-demographic trends on income inequality over the past two to three decades. The main socio-demographic trends in Hungary were largely in line with OECD-wide changes. Family structures are becoming increasingly complex and there is a growing disconnect between nuclear families and households. There has been a general retreat from marriage and a growth in both cohabitation and multigenerational households, as well as in the share of single person households. Births outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Decomposing the overall change in household earnings inequality among working-age households with at least one earner for 23 OECD countries for periods from (mostly) the mid/late 1980s to the mid 2000s, it found that assortative mating and changes in household structure contributed to greater inequality in household earnings, but to a much lesser extent than changes in men's earnings dispersion and men's and women's employment rates. More recently OECD (2020) and Förster and Vindics (2022) carry out a similar analysis across many OECD countries and again conclude that demographic composition plays only plays a minor role in explaining changes in household market income inequality. Harkness (2013) presents a comparative analysis of the impact of increasing women's labour force participation on household earnings inequality.…”
Section: Background and Literaturementioning
confidence: 72%
“…Decomposing the overall change in household earnings inequality among working-age households with at least one earner for 23 OECD countries for periods from (mostly) the mid/late 1980s to the mid 2000s, it found that assortative mating and changes in household structure contributed to greater inequality in household earnings, but to a much lesser extent than changes in men's earnings dispersion and men's and women's employment rates. More recently OECD (2020) and Förster and Vindics (2022) carry out a similar analysis across many OECD countries and again conclude that demographic composition plays only plays a minor role in explaining changes in household market income inequality. Harkness (2013) presents a comparative analysis of the impact of increasing women's labour force participation on household earnings inequality.…”
Section: Background and Literaturementioning
confidence: 72%